Argentine Chaotic Term Length Series in an American Historical Context: Part II: Complex System Analysis (Journal of Advanced Research in Social Sciences, 2023)
The political stability of a government system is crucial for achieving social, economic, and cultural growth of a people. Among other things, political stability depends on the norms that come from a state of rights. Several metrics have been proposed to measure political stability, such as the weighted sum of the number of revolutions or the index defined by the World Bank comprising 72 variables, which include subjective concepts, numerical parameters, and other variables. Therefore, it must be applied carefully to individual countries or to compare countries. No definitions in the related literature directly consider cultural factors and are limited to quantifying their practical effects, such as numbers of strikes or manifestations against a government. Concepts such as contempt for authority have not been directly quantified. In this part, we present two more indicators that account for the contempt for authority and permit a rapid quantitative and visual analysis of the political stability of a country or province throughout its history. They are, the social stability index that allows the general quantification of the social stability level at a historical moment, and the phase planes that graphically show the predominant chaotic system. These tools manifest the behavior patterns that affect the political stability of a country or province. Finally, we perform an in-depth analysis of the indicators for the Republic of Argentina between the 16th and 21st centuries, with the historical context of the more important Spanish and British colonization of the American continent. The results indicate 1) the permanence of socially toxic behavior patterns in Argentina and other Latin American countries, 2) inherited cultural causes could explain the high political instability in Argentina over the last 500 years and 3) a succession of singles term length by rulers during decades could be used to stabilize a country.